Attitudes towards lung cancer screening in socioeconomically deprived and heavy smoking communities: informing screening communication - Quaife, Samantha L. (Health Expect, 2016)
BACKGROUND: While discussion continues over the future implementation of lung cancer screening, low participation from higher risk groups could limit the effectiveness of any national screening programme. OBJECTIVES: To compare smokers’ beliefs about lung cancer screening with those of former and never smokers within a low socioeconomic status (SES) sample, to explore the views of lower SES smokers and ex‐smokers in‐depth, and to provide insights into effective engagement strategies. DESIGN, SETTING AND PARTICIPANTS: Using proactive, community‐based recruitment methods, we surveyed 175 individuals from socioeconomically deprived communities with high smoking prevalence and subsequently interviewed 21 smokers and ex‐smokers. Participants were approached in community settings or responded to a mail‐out from their housing association. RESULTS: Interviewees were supportive of screening in principle, but many were doubtful about its ability to deliver long‐term survival benefit for their generation of “heavy smokers.” Lung cancer was perceived as an uncontrollable disease, and the survey data showed that fatalism, worry and perceived risk of lung cancer were particularly high among smokers compared with non‐smokers. Perceived blame and stigma around lung cancer as a self‐inflicted smokers’ disease were implicated by interviewees as important social deterrents of screening participation. The belief that lungs are not a treatable organ appeared to be a common lay explanation for poor survival and undermined the potential value of screening. CONCLUSIONS: Attitudes towards screening among this high‐risk group are complex. Invitation strategies need to be carefully devised to achieve equitable participation in screening.